(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
This article analyses a particular class of Roman Age furnishings: couches decorated with bone and ivory, so as to indicate their typological features and the area of their diffusion. Furthermore, differently from what has been discussed only marginally in the past, a distinction has been made between examples coming from dwellings and those from a funerary context in order to identify the specific characteristics of each particular type. A census of couch in bone and ivory originating in non-funerary contexts, which may have been used as dining couches in the triclinium or as sleeping beds in cubiculi in the domus, has shown that examples are rather rare and almost exclusively comprised of rising head and foot boards, the finials in particular; these were predominantly of two types: heads of waterbirds and Silenus heads. A more detailed analysis of findings has been made for the Cisalpine area with a direct comparison between those found in necropolis and those coming from a domestic environment. (traduzione di Virginia Ridsdale).